Pengaruh Metode Mind Map Terhadap Ketrampilan Berfikir Kreatif Dan Kemampuan Berkomunikasi Tentang Fisika Siswa Kelas VII SMP Negeri 1 Biromaru - Salfina Salfina; Amiruddin Hatibe; Marungkil Pasaribu (Mitra Sains, 2015)
The objectives of the research are 1) to test the significant difference creative thinking between the students who were taught by using Mind Map Method and they who were taught by using Conventional Method on object change around us; and 2) to test the significant difference of communication ability of the students who were taught by using mind map method and those who were taught by using conventional method on object change around us. The design of the research is Quasi Experimental research design in which it employs purposive sampling design. The sample of the study is the grade VII C consisting of 32 students and the grade VII D consisting of 33 students of the 2014/2015 academic year. The data were collected by using observation check-list and test. The researcher analyzes data by using SPSS program. The result of the study indicates that the score t count> t table (3,50 > 1,998) and sig = 0,001 (0,001 < 0,05); it is found that there is the difference of thinking ability between the students who were taught by using creative thinking skill method and conventional method. Meanwhile, it is found that the result of the posttest on students’ communication skill so t count> t table (3,14 > 1,998) and sig = 0,003 (0,003 < 0,05). It is indicates that there is the difference in communication ability between the students who were taught by using mind map method and the students who were taught by using conventional method. Based on the result of study, it is stated that there is an effect of mind map method toward students’ creative thinking skill and students’ physics communication ability at grade VII student at SMP Negeri 1 Biromaru.